Análisis Jurídico y Doctrinario del Interés Superior de los menores de edad con Discapacidad y su vulneración cuando sus padres son despedidos de su trabajo - Pardo Castillo, Jorge Mairoben (2023)
The present degree work is entitled: “Legal and doctrinal analysis of the principle of the best interest of minors with disabilities and its violation when their parents are fired from their job”, and its interest in research and realize an analysis due to the violation of the principle of best interests of the minors with disabilities at the moment their parents or legal representatives are dismissed from their jobs, which causes direct consequences that directly affect these minors with disabilities, who are in a situation of double vulnerability, due to the defenselessness of their rights, that prevents them from having an adequate integral development. The study carried out, shows that untimely dismissal of the workers substitute alters the emotional stability and physical health of children and adolescents with disabilities, because for this reason, they aren’t being allowed adequate growth and due to their condition, the rights that are proper to children are seen in a state of defenselessness, and, therefore, their best interests of the child are affected, therefore with the present investigation, it’s hoped that a dignified life can be guaranteed to minors with disabilities and reinforced job stability for their parents or legal representatives. In the present titling work, the use and application of materials and methods that allowed its development was made for which surveys and interviews were carried out with legal professionals, whose results served to propose the elaboration of a legal proposal, with the purpose of guarantee the rights of children and adolescents with disabilities to achieve the effective exercise of their best interests, which is being violated due to the dismissal of their parents or legal representatives.